Analysis on Soy-Yamgurt Potential as Antidiabetic in Streptozotocin-Nicotinamide Induced Rats - Jessica Kwanariesta; Herla Rusmarilin; Ismed Suhaidi (Talenta Publisher, 2018)
This study was conducted to determine the potential of soy-yamgurt probiotics drink from the mixture of yam and soy extract with a ratio of 1: 1 in reducing the fasting blood glucose level of rats induced by streptozotocin-nicotinamide. Based on the analysis of chemical and phytochemical characteristics of soy-yamgurt, it was found that it has water content (80.97%), total solids (18.85%), protein content (11.95%), total lactic acid (1.03%), viscosity (20.56 Pa.s), lactic acid bacteria (10.22 log CFU/g), fiber content (0.98%), IC50 value (44.99 Î¼g/ml), total phenol (711.90 Î¼gGAE/g) and total flavonoids (1345.73 Î¼gQE/g). The in vivo test used thirty 10-16 week old male Wistar rats with an average weight of 160-200 g divided into 5 groups: P1 (control), P2 (streptozotocin-nicotinamide), P3 (glibenclamide of 0.45 mg/kg body weight), P4 (3 ml of soy-yamgurt) and P5 (3.5 ml of soy-yamgurt).The results showed that the soy-yamgurt at the doses of 3 ml/160 g body weight and 3.5 ml/160 g body weight for 4 weeks in streptozotocin-nicotinamide-induced rats had significantly (P<0.01) lowered blood glucose levels and increased their weight.